502 Late-Breaking: Tongue Rolling Behavior in a Large U.S. Dairy Herd. (8th October 2021) - Robbins, Jesse; Paros, Mike; McCandless, Kelly
Abstract: Stereotypic behavior is repetitive, invariant behavior with no obvious goal or function and may indicate negative welfare. Non-nutritive oral behaviors are the most common form of stereotypic behavior in captive ungulates and these include tongue rolling where the cow's tongue is extended, moving inside and outside of the mouth while the cow is not eating. We assessed the prevalence of tongue rolling in a large commercial dairy herd located in the United States by video recording cattle (n = 10, 000) during three consecutive milkings on two rotary milking parlors. Associations between tongue rolling behavior, breed, age, days in milk, pregnancy status and milk production were assessed. In total, 29% percent (2, 931) of cows were observed tongue rolling on the rotary parlor during at least one milking; 6% (613) were observed tongue rolling during two milkings; and 1.6% (164) were observed tongue rolling during all three sampling periods. Breed was the only variable associated with tongue rolling in the rotary parlor with nearly twice the proportion of Jersey (33%) vs Jersey X Holstein (17%) exhibiting tongue rolling behavior (P < 0.0001). The higher incidence of tongue rolling among Jersey vs Jersey X Holstein cattle within a shared environment suggests a strong genetic component that warrants further investigation. Validated sampling strategies for assessing tongue rolling in dairy cattle are needed.